Genetic diversity and pathogenicity of the grey mould fungus Botrytis - Hahn, Matthias (My University, 2017)
Genetic diversity and pathogenicity of the grey mould fungus Botrytis Botrytis spp., causes pre- and postharvest decay on strawberry crops. Botrytis spp. isolates from several German strawberry-growing fields, which received several fungicide treatments against Botrytis per season, were analyzed to determine their sensitivity against botryticides.
Keywords: Botrytis cinerea; Botrytis